Weakness in investment growth: Causes, implications and policy responses - M. Ayhan Kose; Franziska Ohnsorge; Lei Sandy Ye; Ergys Islamaj (Koç University-TÜSİAD Economic Research Forum (ERF), 2017)
Investment growth in emerging market and developing economies has slowed sharply since 2010. This paper presents a comprehensive analysis of the causes and implications of this slowdown and presents a menu of policy responses to improve investment growth. It reports four main results. First, the slowdown has been broad-based and most pronounced in the largest emerging markets and in commodity exporters. Second, it reflects a range of obstacles: weak activity, negative terms-of-trade shocks, declining foreign direct investment inflows, elevated private debt burdens, heightened political risk, and adverse spillovers from major economies. Third, by slowing capital accumulation and technological progress embedded in investment, weak post-crisis investment growth has contributed to sluggish growth of potential output in recent years. Finally, although specific policy priorities depend on country circumstances, policymakers can boost investment both directly, through public investment, and indirectly, by encouraging private investment, including foreign direct investment, and by undertaking measures to improve overall growth prospects and the business climate.
Keywords: E22; F2; F6; O1; O4; 330; emerging markets; developing economies; investment slowdown; policy space; infrastructure investment; monetary policy; fiscal policy; structural reforms